USE OF BIOLOGICALLY ACTIVE SUPPLEMENTS FOR RECOVERY IN SAMBO ATHLETES DURING THE SPORTS EXCELLENCE STAGE - Gazieva Zebunniso Yusubjanovna (Innovate Conferences, 2025)
In the modern stage of high-performance sports development, the recovery process is recognized not only as a phase of rest but as an integral part of training adaptation, particularly in physically and mentally demanding disciplines like Sambo. Athletes in the stage of sports excellence often train under high physiological and psychological loads, with frequent sessions of sparring, strength training, and tactical drilling, which lead to significant muscular microtrauma, central nervous fatigue, and depletion of biochemical recovery resources. In such conditions, the role of scientifically grounded recovery support becomes a cornerstone of long-term athletic development and injury prevention. One of the most promising directions within recovery strategies is the application of biologically active supplements (BAS), which can enhance metabolic recovery, optimize hormonal balance, reduce inflammation, and accelerate muscle regeneration.